Farmer Participation in IP400 Rice Cultivation in Kebakkramat District Karanganyar Regency - Naomi Natalia Widiastuti; Eny Lestari; Putri Permatasari (Prospect Publishing, 2023)
IP400 program is one of the efforts to increase national rice production. Farmer participation is an indicator of the success of the IP400 program. This study aims to describe the socio-economic characteristics of farmers, determine the level of farmer participation, and analyze the relationship between the socio-economic characteristics of farmers and the level of farmer participation. The method used is a descriptive quantitative data analysis method in the form of rank spearman. The results showed that the majority of respondents were of productive age, had junior high school education, attended 5-6 counseling sessions and 3-4 training sessions a year, cultivated 3,001-4,500 m² of land, worked as farmers for 16-25 years and implemented IP400 1-2 years, an average income of IDR 5,000,000,00 per planting season, the role of extension agents as motivators, educators, and dynamists is very high, while the role of extension workers as facilitators is quite high; the level of participation is categorized as high at all three stages; there is a significant relationship between the socio-economic characteristics of farmers and the level of farmer participation, except for the formal educationf and land area.